NILAI PENDIDIKAN DALAM TORTOR SIRINTAK HOTANG PADA MASYARAKAT SIMALUNGUN - Rismanauli Purba (Universitas Negeri Medan, 2017)
This study aims to determine how the value of education contained in tortor Sirintak Hotang in Simalungun society. Time used in this study to discuss the value of education in tortor Sirintak Hotang in Simalungun for 2 months from the month of July 2016 until August 2016. The research is Pematang Raya sub-district , North Sumatra . Analysis of the data in this study using quantitative descriptive , to complete the data in this study , the authors conducted a field observation , interviews and documentationIn accordance with the understanding of the value of education in tortor Sirintak Hotang is work to foster public personality suitable values. Educational value contained in tortor Sirintak Hotang namely : ( a) Discipline : Discipline is the act of a person in complying with the rules applicable in public life.As for the kinds of discipline that is included in tortor Sirintak Hotang namely a. cooperation / mutual help , responsibility , never showed a lazy attitude to work , time discipline , a sense of belonging , a loyal neighbor and work groups . ( B ) Confidence : Confidence is assured on the ability and self-assessment in the conduct and beliefs on what she is doing . As for the kinds of confidence in the range of motion Tortor Sirintak Hotang namely : brave , always optimistic in doing the job , had a higher spirit , has the mental strength, have a high responsibility on himself . ( 3 ) Constancy of the soul: the soul is the strength or firmness is a provision in the soul . As for the kinds of mental firmness in the range of motion tortor Sirintak Hotang namely : Patience in the face of obstacles , self-sacrificing .